Improve Students' Numeracy Skills Using Learning Videos - Apriliawan, Putu Andre; Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic requires elementary school students to carry out online learning, but there are many obstacles to online learning, one of which is the mathematics learning process. This study aims to create a learning video to count and develop a learning video to count for elementary school students whose validity has been tested using the ADDIE development model. The subjects in this study were two media experts, two material experts, and two practitioners. The data collected are qualitative and quantitative. The data collection method used is a questionnaire method and measures the validity of the video learning counting using a rating scale instrument. This research produces a numeracy learning video tested for validity with an overall average validation score for learning videos is 4.78, and the average material validation score is 4.87. It means that the counting learning videos developed are classified as very good. Therefore, numeracy learning for first-grade elementary school students is valid and feasible to develop and taught to students.